Work Readiness of Graduates Responding to User Needs for a “Ready to Work” Workforce from University Perspective - Sartika, Didi; Nengsi, Ayu Rahma (Idarah (Jurnal Pendidikan dan Kependidikan), 2022)
There is a fundamental difference in the concept of "ready to work" between the user perspective and the university, especially for prospective graduates who will enter the workforce. The research aims to provide an assessment of the job-readiness of prospective graduates from a university perspective. Job readiness of prospective graduates is assessed based on four aspects: work competence, personal intelligence, social intelligence, and organizational intelligence. The research uses the Mixing method by conducting interviews, distributing the work readiness scale (WRS) instrument developed by Caballero, and making additional modifications to suit the needs. The instrument was filled out by 64 respondents, 8 men and 56 women, spread over 4 study programs at Faculty of Tarbiyah, IAIN Takengon. Job readiness assessment of prospective graduates shows a good quantitative for all aspects measured. The percentage figures show that, on average, each aspect occupies more than 50%. Specifically, the communication skills section, quantitative assessment, and interviews reveal conditions that require special attention in communicating effectively, both oral and written communication. All aspects are assessed to represent the university's perspective in preparing its graduates to have all competencies they should have when entering the work environment. Some shortcomings are not denied. Universities should improve themselves to produce high-quality graduates to align themselves with user / employers needs.